Physiological Importance of Apan Vayu in Mutranishkramanprakriya in Relation to Micturition Reflex - Sharma, Richa; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is an ancient Indian system of medicine whose major goal is to keep healthy people well and cure diseased people. That is why, from ancient times, people from all over the world have been looking to India. Health, according to Ayurveda, is a state in which the dosha, agni, dhaatu, mala, and all physiological processes are in a homeostatic state, and the soul, sense organs, and mind are all in a state of absolute wellbeing. The Vatadosha is the most significant of the three doshas, and it is in charge of controlling all types of movements. Aahara is turned into saara and kitta part when the food is digested by agni with the help of samanavayu. With the harmonization of other Prana and Vyanavayus, apanavayu eliminates the kitta part of food. In pakvadhana, the apanavayu passes through the sroni (pelvis), basti (urinary bladder), medhra (external genital equipment of each sex), and uru (thighs). It aids samirana (flatus), sakrit (feces), mutra (urine), sukra (semen), garbha (foetus), and artava (menstrual fluid) removal.An attempt has been made in this article to comprehend the physiological significance of apanvayu in micturition. The core resources for this study were gathered from Ayurvedic classics with available commentaries, as well as modern medical science text books for a better grasp of the subject.